A bifactor analysis of goal difficulty and commitment in athletes` imagery ability - Lee, S.; Horino, H.; Uhm, J. P. (International Journal of Sport Psychology, 2026)
This study investigated the relationships between goal difficulty, goal commitment, and sport imagery ability using a bifactor model for the Japanese cultural concept of ganbaru across different competitive levels. Eight hundred Japanese collegiate athletes competing at local, regional, national, and international levels participated in the study. The results indicated that goal difficulty did not vary across competitive levels, whereas goal commitment and four types of imagery ability (skill, strategy, goal, and mastery imagery) showed significant differences. The bifactor analysis using structural equation modelling revealed different patterns across competitive levels. These findings suggest that while goal difficulty may hinder imagery generation, goal commitment contributes significantly to imagery ability, particularly at the international level. Moreover, ganbaru appears to influence imagery ability at lower and intermediate levels of competition (local, regional and national). Thus, athletes` roles of goal difficulty and commitment influence imagery generation, and cultural background can have a significant impact.